K+-selective microelectrode study of internally dialyzed squid giant axons. - Fong, C N (1988)
Intracellular potassium activity, (aK)i, and axoplasmic K+ concentration, [K+]i, were measured by means of K+-selective microelectrodes and atomic absorption spectroscopy, respectively, in squid giant axons dialyzed with K+-free dialysis solution and bathed in K+-free artificial sea water. (aK)i measurements indicated that axoplasmic free K+ could be depleted by dialysis, whereas [K+]i measurements on axoplasm extruded from these axons suggest substantial retention of K+ (15.5 +/- 1.7 mmol/kg axoplasm K+; n = 9). In comparison, [K+]i in axoplasm extruded from freshly dissected axons was 330 +/- 16 mmol/kg axoplasm (n = 6). These data suggest that approximately 5% of the axoplasmic K+ ions are not easily removed by dialysis and that these ions are either bound to macromolecular sites or sequestered into membrane-enclosed organelles.